A 2.4-GHz RF CMOS transceiver for wireless sensor applications - Carmo, João Paulo Pereira (2008)
The paper describes a radio frequency transceiver designed in UMC RF 0.18 µm CMOS process. This process has a poly and six metal layers, allowing the use of integrated spiral inductors (with a reasonable quality factor), high resistor value (a special layer is available) and a low-power supply of 1.8 V. This RF CMOS transceiver will be applied to implemented a wireless sensors network in a wireless electronic shirt for helping health professionals with rapid, accurate and sophisticated diagnostic concerning cardiopulmonary disease in order to evaluate the presence of breathing disorders in free-living patients. Without proper design, communication will increase network power consumption significantly because listening and emitting are power-intensive activities. Thus, in order to optimise power consumption, it was included in the design of the RF transceiver, the use of control signals. With these control signals it is possible to enable and disable all the transceiver subsystems. These signals allows for example to switch off the receiver when a RF signal is being transmitted, to switch off the transmitter when a RF signal is being received, and to put the transceiver in sleeping mode when neither RF signals are being transmitted, nor being received.